Interpretation and Reporting of Coronary Arteries in Transposition of the Great Arteries: Cross-sectional Imaging Perspective. Issue 4 (July 2018) - Swanson, Sara K.; Sayyouh, Mohamed M.; Bardo, Dianna M.E.; Ghadimi Mahani, Maryam; Lu, Jimmy C.; Dorfman, Adam L.; Agarwal, Prachi P.
Abstract : Knowledge of coronary artery nomenclature in transposition of the great arteries is essential, given the increasing population of adults with congenital heart disease and greater utilization of imaging in these patients. This article reviews appropriate terminology for describing coronary artery anatomy, commonly encountered coronary artery patterns, and postoperative coronary complications in the setting of transposition of the great arteries.